(untitled) (Quinto Sol, 2022)
This work falls within the field of studies on repression and dialogues especially with the lines of research that explore the existing articulations between the legal/illegal and visible/clandestine dimensions of State terrorism. It analyzes, in particular, the role of military justice within the repressive plots deployed at a regional/local scale during the last Argentine military dictatorship. The focus of inquiry is on the specific practices of the actors; in the strategies launched by the military auditors in order to exercise repression, hide certain procedures of the Armed Forces and exhibit others. The work of the military justice is approached without losing sight of the relationship it had with other state bureaucracies and its articulation with the media consubstantiated with the objectives of the dictatorship. The documentary corpus of the investigation includes judicial files, files of members of the Armed Forces, military summaries, press and regulations referring to the administration of military justice.